La distruzione di “possibile” e “reale” nel giovane Heidegger - Corbella, Giuditta (Bollettino Filosofico, 2020)
The paper explores the connection between facticity and destruction by taking into account Heidegger’s theory of modalities and his understanding of “possible” and “real”. It follows the dismantling of Augustine, Aristotle and Leibniz carried out by Heidegger between 1919 and 1928. Keywords: Destruction, Heidegger, Modalities, Possible, Real